nformation Technology and Applications Proceedings of the 2014 International Conference on Information Technology and Applications (ITA2014), Xi'an, China, 8-9 August 2014 - Li, Xiaolong (CRC Press/Balkema, 2015)
Information Technology (IT) is the application of computers and telecommunications equipment to store, retrieve, transmit and manipulate data, often in the context of a business or other enterprise. IT has become one of the most fundamental technologies in today's social life, and there are many unsolved issues related to IT and its applications.This edited volume on the broad area of IT covers information processing methods and techniques, information theories, information systems, information retrieval, information storage, computer networks, algorithms, databases and the Internet of Things